Good looks, mate value, flirting capacity, and choosiness: Exploring additional pathways to singlehood - Apostolou, Menelaos; Michaelidou, Ellie (Studia Psychologica: Theoria et praxis, 2024)
Many individuals are single because they encounter difficulties in attracting an intimate partner. Various factors, such as flirting capacity and self-esteem, could potentially predict singlehood. However, these factors are interconnected and have indirect associations with singlehood. The current study has attempted to identify these associations by analyzing a database derived from a sample of 1,432 Greek-speaking participants. Our analysis examined singlehood in general as well as involuntary singlehood, separately for men and women. Specifically, we have identified four pathways for women: 1) Higher mate value was associated with greater self-esteem, which, in turn, was associated with an increased flirting capacity. This was correlated with a higher probability of being in an intimate relationship rather than being single. 2) Furthermore, higher mate value was associated with increased self-esteem, which, in turn, was associated with greater choosiness. This was linked to a lower probability of being in an intimate relationship than being involuntarily single. 3) Additionally, higher scores in self-perceived good looks were associated with higher mate value, which, in turn, was associated with an enhanced flirting capacity. This was connected to a higher probability of being in an intimate relationship rather than being single. 4) Finally, higher scores in self-perceived good looks were associated with higher mate value, which, in turn, was associated with greater choosiness. This was associated with a lower probability of being in an intimate relationship than being single. On the other hand, no significant pathways were found for men.